2001
DOI: 10.1002/ana.69.abs
|View full text |Cite
|
Sign up to set email alerts
|

Genome scan of idiopathic generalized epilepsy: Evidence for major susceptibility gene and modifying genes influencing the seizure type

Abstract: Idiopathic generalized epilepsy (IGE) is a common, complex disease with an almost exclusively genetic etiology but with variable phenotypes. Clinically, IGE can be divided into different syndromes. Varying lines of evidence point to the involvement of several interacting genes in the etiology of IGE. We performed a genome scan in 91 families ascertained through a proband with adolescent-onset IGE. The IGEs included juvenile myoclonic epilepsy (JME), juvenile absence epilepsy (JAE), and epilepsy with generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
5
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(112 citation statements)
references
References 19 publications
(27 reference statements)
8
97
5
2
Order By: Relevance
“…Similarly, linkage studies have identified loci linked with specific IGE subtypes (Greenberg et al, 1988; Liu et al, 1996) and others loci linked to cohorts with a variety of IGE syndromes (Sander et al, 2000c; Kinirons et al, 2008). Under a more complex model, these findings could reflect the possibility that individuals within some families may possess additional genetic variants which influence phenotypic expression, a hypothesis previously suggested by Durner et al (2001).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Similarly, linkage studies have identified loci linked with specific IGE subtypes (Greenberg et al, 1988; Liu et al, 1996) and others loci linked to cohorts with a variety of IGE syndromes (Sander et al, 2000c; Kinirons et al, 2008). Under a more complex model, these findings could reflect the possibility that individuals within some families may possess additional genetic variants which influence phenotypic expression, a hypothesis previously suggested by Durner et al (2001).…”
Section: Discussionmentioning
confidence: 62%
“…A large amount of recent research has thus focused on the use of both association and linkage studies to detect pre-disposing variants and loci. Although a number of positive associations (Sander et al, 1997a, 2000a, 2000b, 2002; Steinlein et al, 1997; Chioza et al, 2001, 2002; Chen et al, 2003; Pal et al, 2003; Vijai et al, 2003; Gu et al, 2004) and loci (Sander et al, 1995, 1997b, 2000c; Durner et al, 1991, 1999, 2001; Liu et al, 1996; Serratosa et al, 1996; Pinto et al, 2004; Zara et al, 1995; Puranam et al, 2005; Elmslie et al, 1997; Greenberg et al, 1988, 2000, 2005) have been reported, few have been replicated with any consistency. In addition, recent work by Hempelmann et al (2007) using 126 multiplex IGE families suggested heterogenous configurations of susceptibility loci associated with different IGE subtypes and seizure types, further highlighting the likely complexity of the situation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Mutations in a voltage-gated chloride channel gene (CLCN2) 4 in the 3q26 region were subsequently found in three families, one with epilepsy with grand mal seizures on awakening (EGMA) and juvenile myoclonic epilepsy (JME), one with EGMA and childhood absence epilepsy (CAE), and one with juvenile absence epilepsy (JAE). Susceptibility loci for idiopathic generalized epilepsy (IGE) have been mapped to chromosomes 3q26, 2q36.1, 14q23 2 and 18q21.1, 6p21.2, 8p11.2.…”
mentioning
confidence: 99%
“…JAE may be linked to chromosome 8, 21, 18, and probably 5 (Sander et al, 1997;Durner et al, 1999Durner et al, , 2001. JAE may be linked to chromosome 8, 21, 18, and probably 5 (Sander et al, 1997;Durner et al, 1999Durner et al, , 2001.…”
Section: Etiologymentioning
confidence: 99%